Product Diversification Strategies in Palm Oil Derivatives and Their Impact on Competitive Advantage: A Literature Review - Septia Nurmita; Nurbit Nurbit; Sri Wahyuni (Journal of Current Research in Management, Policy, and Social Studies, 2024)
The global palm oil industry has undergone significant transformation as market volatility, sustainability pressures, and technological advancements reshape value chain dynamics. One of the most prominent strategic responses among plantation firms and downstream processors is the diversification of palm oil derivative products. This literature review synthesizes peer-reviewed studies published between 2013 and 2024 to examine how product diversification strategies contribute to competitive advantage in the palm oil sector. The review explores various forms of diversification, including downstream processing into oleochemicals, biofuels, specialty fats, food additives, and emerging bioproducts such as bioplastics and green surfactants. The findings demonstrate that diversification enhances competitive advantage through value addition, increased market access, innovation capability, and greater resilience to commodity-price fluctuations. The review also highlights the importance of technological capability, research and development investment, sustainability certification, and strategic partnerships in enabling successful product diversification. Despite these advantages, challenges persist in the form of volatile global regulations, sustainability-driven trade barriers, investment risks, and limited technological readiness in some producing countries. The synthesis concludes that product diversification is a central competitive strategy that can strengthen both economic and environmental sustainability of the palm oil industry when supported by innovation ecosystems, integrated supply chains, and responsible governance. Further research is needed to explore techno-economic feasibility, circular-economy integration, and the long-term sustainability impacts of emerging palm-based bioproducts.